Analisis Bibliometrik Perkembangan Penelitian Kebijakan Kebakaran Hutan dan Lahan di Indonesia - Ahmet Vahlevi; Azhar Azhar (Mahesa Research Center, 2024)
The purpose of this study is to analyze research trends related to the development of fire policy research in Indonesia. To process and analyze the topic and content of the article, this study uses bibliometric analysis and content analysis from the Google Scholar database. In addition, bibliometric maps are created with the Vosviewer application. The findings show that the most publications made in 2022 are 40% and each year has an increase in research. In 20 journals clarified and analyzed show problems related to forest and land policies consisting of settlements, ecosystem damage, increasing carbon emission problems, global public health, overlapping views of policies related to restoration areas/maps, overlapping views of policies related to restoration areas/maps, budget factors each year, budget factors each year, lack of community participation in the process of implementing all policies. The bibliometric method can be used to analyze publication trends related to the